Beyond formalism naming and necessity for human beings - Rosenberg, Jay F. 1942-2008 (Temple Univ. Press, 1994)
Rosenberg concludes with a critical reassessment of widely accepted views regarding the relationships among natural languages, mathematical formalisms, and philosophical commitments. The culmination of twenty years' reflection, Beyond Formalism is an original and sophisticated book of importance to both philosophers and linguists